Pandangan Ulama Tentang Upah Nadzir Wakaf (Studi Analisis Pasal 12 UU Nomor 41 Tahun 2004) - Muhammad Abdulah Subekhi; Zaki Mubarok (Universitas Wahid Hasyim Semarang, 2021)
Economic welfare is the dream of every human being, including Muslims, one of the means is through waqf, but its existence is still not widely explored. This is due to the lack of professional nadzir in Indonesia. So through Law No. 41 of 2004 on waqf, especially in Article 12, the Government sets the wages of waqf nadzir, the hope is that nadzir can work professionally. This research is a library research that aims to express the opinion of ‘ulama about nadzir wages and then conclude it. Data collection is conducted through library studies and then qualitatively analyzed by descriptive methods. All ‘ulama agreed that wakif has the right to determine how much wages will be given to nadzir. while the Judge is only entitled to determine the wages of nadzir according to the applicable law. However, if there is no provision from either the wakif or the judge, while nadzir does not submit to the judge, then the ‘ulama differ in opinion. Hanafi and Maliki ‘ulama agreed that judges have the right to determine the wages of nadzir with standard wages. While shafi'i ‘ulama have a difference of opinion that nadzir does not get wages unless it requires, nadzir can take wages but only a little and nadzir can take standard wages whether in need or not. Dissent also occurs in hanbali ‘ulama, if nadzir works with the intention not to stabilize wages then it should not take wages, but if the intention to take wages then there is a difference of opinion that nadzir can take wages either need or not, nadzir can take wages to simply meet his needs, or nadzir can take standard wages.